2018
DOI: 10.1259/bjr.20170845
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic MRI for bowel motility imaging–how fast and how long?

Abstract: A temporal resolution of at least 1 fps and a scan duration of at least 15 s is necessary in breath-hold scans for consistent motility observations. The majority of small bowel motility studies to date are in line with these requirements. Advances in knowledge: This study suggests the minimum temporal resolution and scan duration required in breath-hold scans to obtain robust measurements of small bowel motility from MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
(31 reference statements)
0
25
0
Order By: Relevance
“…No differences were found in the higher frequency range (11)(12)(13)(14)(15)(16)(17)(18)(19) contractions per minute), which primarily contains breathing motion, with an exception at 20 contraction per minute. No differences were found in the higher frequency range (11)(12)(13)(14)(15)(16)(17)(18)(19) contractions per minute), which primarily contains breathing motion, with an exception at 20 contraction per minute.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…No differences were found in the higher frequency range (11)(12)(13)(14)(15)(16)(17)(18)(19) contractions per minute), which primarily contains breathing motion, with an exception at 20 contraction per minute. No differences were found in the higher frequency range (11)(12)(13)(14)(15)(16)(17)(18)(19) contractions per minute), which primarily contains breathing motion, with an exception at 20 contraction per minute.…”
Section: Discussionmentioning
confidence: 93%
“…15,17 For inclusion in this study, we selected all participants that did not receive bowel preparation, resulting in the enrollment of sixteen healthy subjects. The study was designed to gain insight in healthy bowel motility quantified with MRI.…”
Section: Volunteersmentioning
confidence: 99%
See 1 more Smart Citation
“…The short observation periods associated with breath‐hold protocols may seem inadequate to measure GI motility, but have shown good initial results and are very practical for clinical use. Recent work showed that in breath‐hold scanning, using a displacement mapping quantification technique (described below), a temporal resolution of at least 1 image per second and duration of 15 seconds is required for robust assessment of motility . Free‐breathing scans provide more information due to longer scanning times, but the breathing artifacts in the scans and the amount of data for processing still pose a burden to handle.…”
Section: Acquisition and Postprocessing Methodsmentioning
confidence: 99%
“…It has been automated for more repeatable and standardized results and it produces very easily readable color maps. The software has been used and validated in several studies 4,7,9,10,13,18,20,22,23,[25][26][27][39][40][41][42] and one software version is commercially available. 43 F I G U R E 1 This figure visualizes the described quantification techniques.…”
Section: Displacement Mappingmentioning
confidence: 99%